Kajian Hidrolis Rencana Tanggul Pengendali Banjir Sungai Batanghari Kecamatan Bungur Kabupaten Lampung Timur - Bagas Arya Hermuda; Didik Kuswadi; Andy Eka Saputra (Jurusan Teknologi Pertanian, 2014)
Hydraulic embankment design done to solved flooding problems that it caused by damage the catchment area, sedimentation, and the capacity of the river was not able to cover the stream during a peak discharge. The purpose of this research were (1) determined the flood discharge design, and (2) made hydraulic embankment design. Steps of research activities were the preparation, survey and topographical measurements, collected hydrological data, processed of topography and hydrology data, counted the design maximum discharge, designed embankment river. The results showed that (1) the existing discharge was 479,745 m3/s, (2) the result of hydraulic design of Batanghari River embankment were the design discharge of return period 50 years was 938,339 m³/s, the base width of the channel (b) by 35,5 m, the depth of flow (h) by 6,5 m, the slope embankment (1:m) by 1:1, height of freeboard by 1.0 m, wide embankment by 4,0m. Keywords: hydraulic embankment design, the river, flooding, the discharge